The Secular State: An Epistemological Approach to The An-Na’im’s Political Thought - Latief, Mohamad; Fadlilah, Ahmad Rizqi; Adityawarman, Rd (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2023)
This article aims to reveal the political thoughts of Abdullahi Ahmed An-Na'im regarding the concept of a secular state. The material object of this study is An-Na'im's political thought in the form of a secular state concept which is reviewed using epistemology as its formal object. The results of this study explain that: first, the basic assumption of An-Na'im's political thought is a post-secularist worldview. Second, the paradigm is anthropocentric positivism. Third, the framework is constitutionalism, human rights, and citizenship. All these three are used by An-Na'im primarily to make sharia relevant to the context of a modern state. Viewed from an Islamic perspective, the epistemology of An-Na'im's political thought is problematic because after all, post-secularism is still rooted in the principle of separation of state and religion. Making post-secularism a basic assumption is a form of confusion in perspective. Making anthropocentric positivism a paradigm also means placing human knowledge as the main truth. Likewise, framing sharia within the framework of constitutionalism, human rights, and citizenship is a step that has the potential to ignore aspects of the maslahat contained in sharia.